Is the Gothic Arch a reliable radiographic landmark for migration percentage in children with cerebral palsy?. (October 2020) - Wek, Caesar; Chowdhury, Piyal; Smith, Christian; Kokkinakis, Michail
Abstract: Introduction: Reimers migration percentage (MP) is the gold standard for measuring hip displacement in children with cerebral palsy (CP). Hip surveillance registries proposed using the top of the Gothic arch (GA) as a modification in patients with acetabular dysplasia because the classical method (CM) described by Reimers may underestimate hip migration. The aim of this study is to assess the inter- and intra-observer reliability of the modified method (MM) versus the CM and identify their effect on the MP. Methods: We performed a retrospective review of 50 children with CP, who had a hip radiograph at our institution between 1st April 2014 and 28th February 2018. All hip radiographs were carefully selected to show the presence of a GA. Four observers measured the MP using the CM and MM for each patient. Interclass coefficient was used to estimate inter- and intra-observer reliability. Results: Inter-observer reliability was excellent for the CM with ICC 0.96 (95% CI 0.94 to 0.97) and good for the MM, ICC 0.78 (95% CI 0.51 to 0.89) p < 0.001. Intra-observer reliability was excellent for both methods raging from ICC 0.94 to 0.99 for the CM and ICC 0.89 to 0.95 for the MM. The mean MP was 19% for the CM and 28% for the MM (p < 0.001). Conclusion: The CM is more reliable than the MM to measure hip migration in children with CP. If the CM is used and acetabular dysplasia with a GA are present on the hip radiograph, then a 9% hip migration underestimation should be considered on decisions for both referral and surgical management. Level of evidence: II